Online Gambling, Legal Prohibition, and Digital Daʿwah: An Islamic Sociological Jurisprudence Approach to Behavioral Legal Reform - Ahamad Muhammad Mustain Nasoha; Muhammad Syafiq Al Hakim; Althaf Dzakwan Alauddin; Farhan Nur Fadilah; Muhammad Dhiaurrahman; Dwi Setyo Jatmiko (Jurnal Manajemen dan Pendidikan Agama Islam, 2026)
The rapid advancement of digital technology has transformed gambling practices from conventional activities into online platforms that are increasingly difficult to regulate and control. This phenomenon creates legal challenges as well as serious social and moral concerns in Muslim-majority communities. In Indonesia, more than 2.37 million active online gambling users were recorded in 2023, with cumulative transactions exceeding IDR 327 trillion, highlighting the urgency of a comprehensive and multidimensional response. This study aims to analyze the prohibition of online gambling in Islamic law and Indonesian positive law, examine the gap between normative prohibition and practical effectiveness, and formulate a behavioral legal reform strategy through the Islamic Sociological Jurisprudence approach by integrating digital daʿwah as a transformative instrument. This research uses a qualitative method with a normative-sociological approach by analyzing primary legal sources, including the Qur’an, Hadith, juristic opinions, and national legislation, as well as secondary sources such as academic literature and policy documents. The findings show that although online gambling is clearly prohibited in Islamic and positive law, enforcement remains limited due to weak value internalization, high digital accessibility, and low public legal literacy. Digital daʿwah is therefore positioned as a strategic bridge between legal norms and digital society.